Short Report: Clinical Cutaneous Leishmaniasis Rates Are Associated with Household Lutzomyia gomezi, Lu. Panamensis, and Lu. trapidoi Abundance in Trinidad de Las Minas, Western Panama - Saldaña, Azael (2013)
American cutaneous leishmaniasis (ACL) transmission patterns have been increasingly associated with domestic and peridomestic environments. Here, we present results from an epidemiological survey of 94 people from 24 households in Trinidad de Las Minas, western Panama. We studied the role of sand fly abundance, housing quality, peridomicile landscape matrix, and vegetation structure on shaping household clinical ACL rate patterns at Trinidad de Las Minas. We found that sand fly abundance was significantly associated with household clinical ACL rates, with a 6% rate increase for each additional Lutzomyia gomezi sand fly found inside a domicile.